Wastewater and landfill leachate testing: acute toxicity biotest results evaluation - Četkauskaitė, Anolda; Vosylienė, Milda Zita; Kazlauskienė, Nijolė; Kalcienė, Virginija (Journal of Environmental Engineering and Landscape Management, 2016)
This diverse review discusses biotest species and results scoring systems, which were applied to aquatic toxicity assessment of effluents/wastewater (WW) and landfill leachate (LL). European and American aquatic toxicity testing is reviewed. An example of Lithuanian research data on LL biotesting with aquatic organisms of different phylogenetic and ontogenetic levels is presented. Acute toxicity WW and LL is assessed on the basis of (L(E)C50, acute Toxic Units (tua), pt values, and, by applying different simple result scoring systems or toxicity thresholds. The differences in legislation and recommendations for biotest application in WW and LL aquatic toxicity testing are compared. It is concluded that WW and LL lowest acute toxicity data (tua value 0.3) should be considered equally as risk to aquatic environment, and technical management decisions should be made. The universal features of toxicity scoring systems, the problems of inventory of old small landfills and cost effective approach are discussed.